The Nucleic acid protocols handbook - Rapley, Ralph (Humana Press, 2000)
Univ. of Hertfordshire, Hatfield, UK. Treasury of all the key molecular biology methods, ranging from DNA extraction to gene localization in situ, needed to function effectively in the modern laboratory. Provides scientific basis of each technique, and a listing of all materials needed, and instructions. For researchers. Softcover, hardcover also available.
Keywords: Molecular Biology; Kyseliny nukleové; molekulární biologie; nukleové kyseliny; Chromosome Mapping; biochemie; mapování chromozomů; Nucleic Acids; biologie; Polymerase Chain Reaction; polymerázová řetězová reakce